FISH FAUNAL DIVERSITY of TURORI RESERVOIR AT TURORI, TQ. OMERGA DIST. OSMANABAD (M.S.) (International Journal of Food and Nutritional Sciences, 2022)
Fish is a most valuable source of proteins and occupied a significant position in the Socio-economicalfabric in most of the countries. Biodiversity is essential for stabilization of ecosystem and protection of overallenvironmental quality. In the present study attempts were made to study the fish faunal diversity of TuroriReservoir at Turori, Tq. Omerga, District Dharashiv, in Marathwada region. Systematic surveys wereconducted during a period of one year (June 2011 to May 2012) It is perennial water bodies, resource forhuman consumption and agriculture. There is no report on the biodiversity of Turori Dam with specialreference to the fish diversity. About 22 species of fish were identified 5 orders and 10 families were recorded.